โรงพยาบาลดึงดูดใจตามการรับรู้ของพยาบาลวิชาชีพโรงพยาบาลลำปาง - อนงค์พร อุปสิทธิ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Magnet Hospital is an excellent management hospital that attracts and maintains highly competent nurses as well as provides safe patient care and excellent services. This descriptive study aimed to explore Magnet Hospital characteristics as perceived by registered nurses working in Lampang Hospital. The sample consisted of 252 registered nurses. The research instrument was the questionnaire that identified quality of nursing organization based on Magnet Hospital characteristics developed by Sangsrijan (2009). The Cronbach’s alpha coefficient of the questionnaire was .98. Data were analyzed by using frequency, percentage, mean and standard deviation. The results revealed that: 1. The overall level of Magnet Hospital characteristics as perceived by registered nurses was at a high level ("X" ̅ = 3.56, SD = 0.42). 2. The level of Magnet Hospital characteristics as perceived by registered nurses in dimension of empirical quality results; new knowledge, innovation and improvements; and exemplary professional practice were at a high level ("X" ̅ = 3.86, SD = 0.47; "X" ̅= 3.69, SD = 0.49; "X" ̅=3.59, SD = 0.45 respectively), whereas transformational leadership and structural empowerment dimensions were at moderate level ("X" ̅ = 3.49, SD = 0.53; "X" ̅= 3.47, SD = 0.45 respectively). It was proposed that the results of this research study could provide directions for hospital and nursing directors to improve appropriate Magnet Hospital characteristics in Lampang Hospital.